Impact of Short Video Marketing on Consumer Behavior in Kathmandu Valley - Dali, Ankita Kumari (Nepalese Journal of Economics, 2025)
This study examines the impact of short video marketing on consumer behavior in Kathmandu Valley. Consumer behavior is the dependent variable. The selected independent variables are interesting content, video duration, scenario-based experience, user participation interaction, and perceived usefulness. The primary source of data is used to assess the opinion of respondents regarding interesting content, video duration, scenario-based experience, user participation interaction, perceived usefulness and consumer behavior. The study is based on primary data of 125 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of the impact of short video marketing on consumer behavior in Kathmandu Valley. The study showed a positive impact of interesting content on consumer behavior. It indicates that interesting content leads to better consumer buying decision. Similarly, the study showed a positive impact of video duration on consumer behavior. It indicates that short runtime of video leads to attract consumer buying behavior in interested field. Likewise, the study showed a positive impact of scenario-based experience on consumer behavior. It indicates that scenario based experience lead to change in consumer behavior. Further, the study showed a positive impact of user participation interaction on consumer behavior. It indicates that better user participation interaction attracts individuals. In addition, the study showed a positive impact of perceived usefulness on consumer behavior. It indicates that perceived usefulness leads to encourage while choosing products.